2010
DOI: 10.1016/j.yjmcc.2010.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and expansion of functionally-competent cardiac progenitor cells directly from heart biopsies

Abstract: The adult heart contains reservoirs of progenitor cells that express embryonic and stem cell-related antigens. While these antigenically-purified cells are promising candidates for autologous cell therapy, clinical application is hampered by their limited abundance and tedious isolation methods. Methods that involve an intermediate cardiosphere-forming step have proven successful and are being tested clinically, but it is unclear whether the cardiosphere step is necessary. Accordingly, we investigated the mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
138
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(152 citation statements)
references
References 37 publications
9
138
1
4
Order By: Relevance
“…5,14 This product has been shown to provide equivalent repair to established cell products with hints of superiority. 10,15 The current work extends previous studies by providing the first unambiguous head-to-head comparison of autologous CACs and CSCs from clinical patients. Although earlier work from our laboratory demonstrated that expanded populations of CSCs from human cardiac samples secrete significant quantities of vascular endothelial growth factor, insulin-like growth factor-1, and hepatocyte growth factor, we used a wide-ranging cytokine protein array to show that CSCs also secrete significant amounts of angiopoietin-1, angiogenin, and inter-leukin-6.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…5,14 This product has been shown to provide equivalent repair to established cell products with hints of superiority. 10,15 The current work extends previous studies by providing the first unambiguous head-to-head comparison of autologous CACs and CSCs from clinical patients. Although earlier work from our laboratory demonstrated that expanded populations of CSCs from human cardiac samples secrete significant quantities of vascular endothelial growth factor, insulin-like growth factor-1, and hepatocyte growth factor, we used a wide-ranging cytokine protein array to show that CSCs also secrete significant amounts of angiopoietin-1, angiogenin, and inter-leukin-6.…”
Section: Discussionsupporting
confidence: 71%
“…CSCs were cultured using standard culture techniques described previously. 10 CACs were isolated from peripheral blood samples using standard techniques. 2,11 Normal human dermal fibroblasts (NHDFs) and human umbilical vein endothelial cells were cultured according to the manufacturer's directions.…”
Section: Cell Culture and Conditioned Mediamentioning
confidence: 99%
“…2A) [15]. Briefly, tissue sections were minced and digested prior to being placed in cardiac explants media (CEM; Iscove's Modified Dulbecco's Medium (Invitrogen), 20% Fetal Bovine Serum (FBS; Invitrogen), 100 U/ml penicillin, 100 μg/ml streptomycin (Invitrogen), 2 mmol/l L-glutamine (Invitrogen) and 0.1 mmol/l 2-mercaptoethanol (Invitrogen).…”
Section: Patients and Cell Culturementioning
confidence: 99%
“…Several studies have been carried out to isolate and characterize cardiac precursor cells (mainly c-Kit + , Sca-1 + , and cardiospheres) from normal and pathologic fetal and adult heart biopsies [12][13][14][15]. Different protocols have been developed to improve CSC isolation methods, resulting in the generation of a specific population of CSCs [16][17][18][19]. In addition to cell sorting and culture of explants, clonogenic expansion of cells has been described as another CSCs isolation method [20].…”
mentioning
confidence: 99%